The use of N-acetylcysteine to prevent further progression of preeclampsia - Indrawan, I Wayan Agung; Farida, Leny (Universitas Airlangga, 2024)
HIGHLIGHTS 1. The generation of free radicals in the placenta leads to endothelial dysfunction, which contributes greatly in preeclampsia.2. N-acetylcysteine have a role in the oxidative stress pathway, helping in glutathione synthesis and as a free radical scavenger.3. N-Acetylcysteine supplementation in women with preexisting preeclampsia had positive effects on oxidative stress biomarkers, laboratory values, and blood pressure. ABSTRACT Objectives: Preeclampsia is a prevalent disorder among pregnant women, characterized by hypertension and proteinuria, leading to serious complications. However, the precise pathophysiology of preeclampsia remains debated. Oxidative stress is believed to play a significant role in its development, and N-acetylcysteine (NAC) is known to influence this pathway. NAC aids in glutathione synthesis, a critical antioxidant, and acts as a free radical scavenger. This study aimed to examine the role of NAC in women with preeclampsia, focusing on its potential therapeutic benefits. Materials and Methods: A comprehensive literature search was conducted using PubMed and ScienceDirect databases, yielding 17 articles from PubMed and 395 articles from ScienceDirect. Reviews were excluded, resulting in 12 articles from PubMed and 89 articles from ScienceDirect. After further screening, 5 articles were selected for review, including 2 human studies and 3 animal studies, to understand the impact of NAC on preeclampsia. Results: Human studies indicated that NAC supplementation reduced the rate of preeclampsia among women at increased risk. Animal studies supported these findings, showing improvements in oxidative stress biomarkers, laboratory values, and blood pressure in models treated with NAC. NAC supplementation was associated with positive outcomes in managing oxidative stress, a key factor in the pathogenesis of preeclampsia. Conclusion: NAC supplementation in women with preexisting preeclampsia has beneficial effects on oxidative stress biomarkers, laboratory values, and blood pressure. These highlight the potential of NAC as a therapeutic intervention for preeclampsia, particularly in women at high risk. However, no significant differences were observed in maternal complication rate between the NAC-treated group and the control group. Further research is needed to fully understand the clinical implications of NAC supplementation and its long-term safety and efficacy in managing preeclampsia.